Decoding the microbial-local immune dialogue in liver cancer: from ecological drivers to precision therapeutics - Xu, Yichi; Wen, Bo; Gao, Nan; Liu, Shu (Frontiers in Oncology, 2025)
The global incidence and mortality rates of liver cancer remain persistently high, attributable to its multifaceted etiology. Recent research has increasingly focused on the interaction between gut microbiota and the liver’s immune system. The gut-liver axis, which connects the gut and liver via the portal vein system and biliary tract, is crucial in maintaining homeostasis; however, dysbiosis can compromise the gut’s barrier function. The gut microbiota exerts influence over hepatic immune cells through various mechanisms, including alterations in microbial composition, production of metabolic products, and the presence of pathogen-associated molecular patterns. These interactions contribute to immune evasion, inflammation, and remodeling of the tumor microenvironment in liver cancer, thereby affecting the efficacy of immunotherapy. Despite these insights, the precise mechanisms underlying these interactions and their potential clinical applications remain inadequately understood. This article aims to review the mechanisms of interaction between the gut microbiota and the local immune response in liver cancer, integrating the latest research advancements. Additionally, it will explore the impact of these interactions on the tumor immune microenvironment, with the objective of providing a theoretical foundation and potential strategies for prevention and therapeutic intervention.